2021
DOI: 10.1021/acs.jafc.1c02591
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of a Novel Aspartic-Type Endopeptidase from Moringa oleifera Seeds and Its Milk-Clotting Properties

Abstract: A novel aspartic-type endopeptidase was previously obtained from Moringa oleifera seeds; however, its specific milkclotting properties have remained unclear. Here, we used various biophysical and molecular simulation approaches for characterizing the structure and function of the aspartic-type endopeptidase. The endopeptidase was preferentially active toward κ-casein (CN) and hydrolyzed it more than calf rennet; however, its ability to hydrolyze α-CN and β-CN was weaker than that of calf rennet. The endopeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Also, the values of the α 2 chain were 2.467 and -2.733, respectively ( Figure 1B ). The larger positive value indicated the greater hydrophobicity, while the smaller negative value indicated the greater hydrophilicity ( 37 ). This result suggested that unwinding yak bone collagen-I could be soluble in water and hydrolyzed by proteases, which was consistent with previous studies ( 21 , 38 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the values of the α 2 chain were 2.467 and -2.733, respectively ( Figure 1B ). The larger positive value indicated the greater hydrophobicity, while the smaller negative value indicated the greater hydrophilicity ( 37 ). This result suggested that unwinding yak bone collagen-I could be soluble in water and hydrolyzed by proteases, which was consistent with previous studies ( 21 , 38 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…High PA leads to low MCI, which directly affects cheese yield, flavor, and texture. 6,11,16 Given that calf chymosin is considered the mosteffective MCE, it is often compared with other alternative coagulants. 4,7 In this study, although the MCI of PsMCE was lower than that of calf chymosin, it was higher than the commercial MCEs from R. miehei, 4 M. pusillus, 19 and Cynara scolymus.…”
Section: Enzymatic Characteristics Of Purified Psmcementioning
confidence: 99%
“…The PsMCE structure was mainly composed of β-sheets, which are consistent with the structure of aspartic proteases from other species. 16,21 The Ramachandran plot analysis of the selected PsMCE structure showed that over 92.7% of the regions residues were within the most favored, 6.1% of the residues were in the additional allowed region, 1.2% of the residues were in the generously allowed regions, and no residues were in the disallowed region (Figure 5B). These results indicate that the structural model of PsMCE is extremely of good quality and can be used for the following analysis.…”
Section: Hydrolysis Of κ-Casein and Cleavage Site Analysismentioning
confidence: 99%
See 2 more Smart Citations